Enhancing 31P NMR relaxation rates with a kinetically inert gadolinium complex. Issue 9 (21st February 2020) - Tear, Louise R.; Maguire, Mahon L.; Tropiano, Manuel; Yao, Kezi; Farrer, Nicola J.; Faulkner, Stephen; Schneider, Jurgen E.
Abstract : The heptadentate gadolinium complex Gd.pDO3A (1.Gd ) generates significant 31 P nuclear magnetic resonance (NMR) relaxation enhancement of biologically relevant phosphate species; adenosine triphosphate (ATP), phosphocreatine (PCr) and inorganic phosphate. Abstract : The kinetically stable heptadentate gadolinium complex Gd.pDO3A (1.Gd ) demonstrates significant 31 P nuclear magnetic resonance (NMR) relaxation enhancement of biologically relevant phosphate species; adenosine triphosphate (ATP), phosphocreatine (PCr) and inorganic phosphate. Gd.pDO3A (1.Gd ) binds these species in fast exchange, enabling the relaxation of the bulk phosphate species in solution. This gives rise to 31 P relaxation enhancements up to 250-fold higher than those observed for 31 P relaxation enhancements with the commercial MRI contrast agent Gd.DOTA (DOTAREM), 2 . Gd.pDO3A-like complexes may have potential applications as 31 P magnetic resonance contrast agents, since shortening the T 1 relaxation time of phosphate species would reduce the time needed to acquire 31 P-MR spectra.